2019
DOI: 10.24246/j.jk.2019.v6.i2.p130-145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Implementasi Kurikulum 2013 Mata Pelajaran Biologi Di SMA Negeri

Abstract: The study intends to evaluate the 2013 curriculum of biological subjects at SMAN 1 Waingapu. Evaluative research is a type of research. Data collection, data reduction, data display, and data conclusion are techniques in data analysis, while data collection techniques are conducted with document studies, observations, and interviews. The principal, Wakasek curriculum, biology teachers, and students are the subject of research. Legitimacy of data by using source triangulation and triangulation method. The evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 2 publications
0
6
0
9
Order By: Relevance
“…However, they need to understand the 2013 Curriculum, learning models, assessment, HOTS questions, and the ability to use information technology in the learning process. Another study stated that teachers needed more curriculum 2013 training in the learning process due to the lack of curriculum 2013 training (Makaborang, 2019). This study found gaps in the learning design, learning process, and learning assessment, especially for affective or attitude assessment.…”
Section: Introductionmentioning
confidence: 85%
“…However, they need to understand the 2013 Curriculum, learning models, assessment, HOTS questions, and the ability to use information technology in the learning process. Another study stated that teachers needed more curriculum 2013 training in the learning process due to the lack of curriculum 2013 training (Makaborang, 2019). This study found gaps in the learning design, learning process, and learning assessment, especially for affective or attitude assessment.…”
Section: Introductionmentioning
confidence: 85%
“…Biology teachers at SMAs in Sungai Kanan District admitted that they could not provide optimal assessments with so many students and such a short amount of time so that biology teachers in SMAs in Sungai Kanan had difficulties and obstacles in conducting assessments with time. limited, it is difficult to carry out an assessment of the learning process because it is less effective (Makaborang, 2019).…”
Section: Understanding Of Biology Teachers In Conducting Assessment O...mentioning
confidence: 99%
“…Sesuai dengan yang tercantum dalam Permendikbud No. 22 Tahun 2016 bahwa untuk memperkuat pendekatan ilmiah (scientific), tematik terpadu (tematik antar matapelajaran), dan tematik (dalam suatu mata pelajaran) perlu diterapkan pembelajaran berbasis penyingkapan/penelitian (discovery/inquiry learning) (Makaborang, 2019;Sudana, 2018). Dengan diberikan proyek kepada siswa yang harus dikerjakan secara berkelompok maka diharapkan keterampilan kolaborasi dari siswa dapat ditingkatkan (Sukmasari & Rosana, 2017;Sumarno, 2019).…”
Section: Pendahuluanunclassified